Effects of The Maxillary Molar Distalization with Zygoma-Gear Appliance on Maxillary Third Molars - Mevlüt Çelikoğlu; Metin Nur; Doğan Kılkış; Mehmet Bayram; Celal Çandırlı (Turkish Journal of Orthodontics, 2012)

(untitled)
Aim:The aim of the present study was to evaluate the effects of a newly produced appliance, named as Zygoma-Gear Appliance (ZGA), on maxillary third molars. We also investigated the effects of ZGA on skeletal, dentoalveolar, and soft tissue measurements.Subjects and Methods:The study group included 10 patients (mean age: 18.3±1.8 years) treated with ZGA system supported with zygomatic anchorage miniplates. The changes due to the distalization were evaluated from the lateral cephalometric films taken before and after distalization by means of Paired t-test.Results:The mean treatment period to achieve a Class I molar relationship was 7.9±3.1 months. The distalization amount of the maxillary molar teeth was 3.8±2.1 mm (p< 0.001) and thus the rate for the distal movement of the molar teeth was 0.50 mm per month. There was a decrease in overjet and inclination of the maxillary central incisor, indicating that there was no anchorage loss by using the ZGA. Maxillary third molars moved distally 1.0±0.9 mm (p< 0.05), with a distal tipping of −7.5±5.5° (p< 0.01). No significant change was observed in the distance of the maxillary third molars to the HRL (−0.5±1.1) (p> 0.05).Conclusions:Maxillary molar distalization without anchorage loss was achieved with ZGA. Maxillary third molars were slight affected by the distalization force.